2001
DOI: 10.1002/eej.1120
|View full text |Cite
|
Sign up to set email alerts
|

New block diagrams using vector signals in the general frame of reference for AC motors with stator core losses

Abstract: SUMMARYThis paper presents new block diagrams for induction and synchronous motors with stator core losses such as eddy-current and hysteresis losses. The proposed block diagrams succeed in realizing simple and clear configurations with physically meaningful vector signals, which are helpful for understanding motor electromagnetic mechanism and useful for designing controllers for them. Vector signals, which are defined in the general reference frame, are utilized as transfer signals between blocks. The propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 11 publications
(30 reference statements)
1
12
0
Order By: Relevance
“…6(b) are used. It is easily confirmed that they are consistent with previously reported results [23][24][25]. The consistency verifies the correctness of the analytical results presented in the previous section.…”
Section: Ac Motor Systemssupporting
confidence: 92%
See 1 more Smart Citation
“…6(b) are used. It is easily confirmed that they are consistent with previously reported results [23][24][25]. The consistency verifies the correctness of the analytical results presented in the previous section.…”
Section: Ac Motor Systemssupporting
confidence: 92%
“…ω 2n is electrical speed of rotor. The circuit equation in (25) can be expressed in the form of (3) such that If evaluated from the viewpoint of current controller for vector control, the induction motor turns out to be a kind of system with vector rotators, which can be shown as in Fig. 6(a) [24].…”
Section: Ac Motor Systemsmentioning
confidence: 99%
“…In the torque system, instead of torque equation (10) we use a simpler representation for AC motors based on stator flux linkage [25,[29][30][31]. In addition, the dynamic characteristic (43) of the mechanical load system (the system includes the rotor and a connected mechanical load) is expressed by using a first-order delay for simplicity.…”
Section: Type-a Vector Block Diagrammentioning
confidence: 99%
“…Such a block diagram in a fixed reference frame can be used immediately as a dynamic vector simulator for the SelE-HFSM [25,[29][30][31].…”
Section: Supplemental Considerationsmentioning
confidence: 99%
See 1 more Smart Citation